2013
DOI: 10.2109/jcersj2.121.205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between crystal structure and oxide-ion conduction in <i>Ln</i><sub>2</sub>Zr<sub>2</sub>O<sub>7</sub> (<i>Ln</i> = Eu, Nd and La) system deduced by neutron and X-ray diffraction

Abstract: Crystal structures of the Ln 2 Zr 2 O 7 (Ln = Nd and La) were refined by the Rietveld analysis of powder neutron diffraction (ND) data at room temperature. La 2 Zr 2 O 7 had a pyrochlore (P)-type structure of almost completely ordered for oxygen vacancy. On the other hand, Nd 2 Zr 2 O 7 had the P-type structure for the oxygen vacancy distributed between the O2 (8b) and O3 (48f ) sites. The Rietveld refinement results of powder X-ray diffraction (XRD) data of Ln 2 Zr 2 O 7 (Ln = Eu, Nd and La) indicated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
(12 reference statements)
1
11
1
Order By: Relevance
“…They suggested a crystal structure model with an anion site mixing P-type structure for the oxygen vacancy distributed over 8b and 48f sites (Note: Ln atoms are located at the origin, i.e., 16c site (0, 0, 0), Zr atoms are located at the 16d site (1/2, 1/2, 1/2), O atoms are located at the 8a site (1/8, 1/8, 1/8) and 48f site (x, 1/8, 1/8), and the 8b site (3/8, 3/8, 3/8) is vacant). Therefore, we adopted this disordered P-type structure with an oxygen vacancy as the crystal structure model (Note: In previous studies, 3) Ln atoms were located at the origin, i.e., 16c site (0, 0, 0), Zr atoms were located at the 16d site (1/2, 1/2, 1/2), and O atoms were located at the O1(8a) site (1/8, 1/8, 1/8) and O3(48f ) site (x, 1/8, 1/8), which is the same crystal structure model as that proposed by Whittle et al 10) ). The oxygen site occupancies (g) of O1(48f ) and O3(8a) were refined together.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested a crystal structure model with an anion site mixing P-type structure for the oxygen vacancy distributed over 8b and 48f sites (Note: Ln atoms are located at the origin, i.e., 16c site (0, 0, 0), Zr atoms are located at the 16d site (1/2, 1/2, 1/2), O atoms are located at the 8a site (1/8, 1/8, 1/8) and 48f site (x, 1/8, 1/8), and the 8b site (3/8, 3/8, 3/8) is vacant). Therefore, we adopted this disordered P-type structure with an oxygen vacancy as the crystal structure model (Note: In previous studies, 3) Ln atoms were located at the origin, i.e., 16c site (0, 0, 0), Zr atoms were located at the 16d site (1/2, 1/2, 1/2), and O atoms were located at the O1(8a) site (1/8, 1/8, 1/8) and O3(48f ) site (x, 1/8, 1/8), which is the same crystal structure model as that proposed by Whittle et al 10) ). The oxygen site occupancies (g) of O1(48f ) and O3(8a) were refined together.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to obtain information of long-range and short-range structures of the pyrochlore compounds with Ln 2 Zr 2 O 7 system. Previously, Hagiwara et al 3) used neutron diffraction to investigate the relationship between crystal structures and oxide-ion conductivity in Nd 2 Zr 2 O 7 (abbreviated NZO) and LZO. They found that LZO has the ideal pyrochloretype (P-type) structure, and NZO has a disordered P-type structure with the oxygen vacancies distributed over 8b and 48f sites at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, x (48 f ) is a single positional parameter to refine in the structure and is known to vary in pyrochlores from 0.319 to 0.343 . A previously reported x (48 f ) value for La 2 Zr 2 O 7 at room temperature is 0.331 (recalculated as ¾− x for comparison with Zr as the origin). La is in distorted cubic coordination and Zr is in distorted octahedral coordination with oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…One might expect similar con ductivity in Nd 2 Zr 2 O 7 , but this compound is not an intrinsic oxygen ion conductor because, according to many previous studies [3,9,10] and present findings, it is ordered by virtue of the larger ionic radius mis match between neodymium and zirconium. Never theless, Hagiwara et al [29] have very recently obtained high conductivity Nd 2 Zr 2 O 7 (2 × 10 -3 S/cm at 700°С), which either was due to an accidental devi ation from stoichiometry or indicates that, optimizing the synthesis procedure and annealing temperature and time, they were able to ensure oxygen disorder in pyrochlore Nd 2 Zr 2 O 7 . According to previous results [2,4], the oxygen vacancy conductivity of the Ln 2 (Zr 2 -x Ln x )O 7 -δ (Ln = Nd, Sm; 0 < x ≤ 0.3) solid solutions is considerably lower than their oxygen interstitial conductivity.…”
Section: Determination Of Excess Oxygen In Thementioning
confidence: 99%